ANALYSIS OF THE INFLUENCE OF BRAND TRUST, BRAND EXPERIENCE, BRAND LOVE & BRAND SACREDNESS ON BRAND FIDELITY ON SKINTIFIC CONSUMERS - Sekarsari, Larasati Ayu; Umrulloh, Ditayatul (Indonesian Journal of Strategic Management, 2025)
This study aims to determine the effect of Brand Trust, Brand Experience, Brand Love and Brand Sacredness on Brand Fidelity in Skintific product users. The research used a quantitative method with hypothesis testing, where data was collected through a questionnaire distributed via google form to 158 respondents who had purchased and used Skintific products. This study used a purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) based on WarpPLS version 7.0. The results of this study indicate that Brand Trust and Brand Experiencer have a significant effect on Brand Love. Brand Love has a significant effect on Brand Sacredness and Brand Fidelity. In addition, Brand Sacredness also has a significant effect on Brand Fidelity in Skintifc product users.